Opportunities and Challenges in Developing Micro, Small and Medium Enterprises from Various Financial Aspects - Fathur Rozi; Abdur Rohman (Managing: Jurnal Bisnis dan Manajemen, 2025)
MSMEs have an important role in the country's economy because they are the only ones who are considered capable of surviving the current storm of trade competition and economic downturn. Many sectors contribute to Indonesia's economic development, but the micro, small and medium enterprise (MSME) sector has a very large contribution. Literature evaluation of books and journals related to research is part of the research methodology. The findings of this research show how broad the financial prospects are for the development of MSMEs, as well as how these opportunities are influenced by several other factors. Meanwhile, funding, marketing and financial problems are obstacles to the development of MSMEs. Based on the study findings, MSMEs can benefit from two different things, namely the first is basic potential, then the second is a policy from the government regarding the type of business developed by MSMEs. Constraints are financing and marketing factors. As many as 17.50% of MSMEs received capital from banks, and 82.50% from non-bank institutions such as individual savings and loan cooperatives, family loans, venture capital and others.